2013
DOI: 10.1364/ao.52.005042
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast transient responses of optical wireless communication detectors

Abstract: In this work, fundamental ultrafast transient responses are studied for optical wireless communication (OWC) detectors. It is shown that material impulse responses, associated with transient photoconductivity, and geometrical input responses, associated with transient optical power, must be considered in tandem when OWC photodetection is pursued with broad spectral and directional characteristics. An OWC detector, composed of GaAs photoconductive gaps in a corner-cube geometry, is fabricated and analyzed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…All three retro-modulated signals are symmetric with respect to the zero-time with a full-width-at-halfmaximum of approximately 120 fs, which is comparable with the pulse durations of both the local 780 nm control beam and the remote 1550 nm signal beams. Thus, it can be concluded that the nonlinear optical beam interaction at the rear interface of the spherical transceiver introduces a nonresonant nonlinearity, which is due to the nonlinear electronic polarization of the glasses (rather than resonant charge-carrier photogeneration and recombination 19 ). When the local 780 nm control beam interacts with the remote 1550 nm signal beam on the rear interface of the spherical transceiver, a transient refractive index increase is established, and the retroreflected signal intensity increases due to the effect of the positive nonlinear coefficient, n 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All three retro-modulated signals are symmetric with respect to the zero-time with a full-width-at-halfmaximum of approximately 120 fs, which is comparable with the pulse durations of both the local 780 nm control beam and the remote 1550 nm signal beams. Thus, it can be concluded that the nonlinear optical beam interaction at the rear interface of the spherical transceiver introduces a nonresonant nonlinearity, which is due to the nonlinear electronic polarization of the glasses (rather than resonant charge-carrier photogeneration and recombination 19 ). When the local 780 nm control beam interacts with the remote 1550 nm signal beam on the rear interface of the spherical transceiver, a transient refractive index increase is established, and the retroreflected signal intensity increases due to the effect of the positive nonlinear coefficient, n 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The 1550 nm signal beam is incident across the three PC switches. The incident signal beam is sampled and summed by an electrical via-hole (not shown) for OWC active downlink reception 4,19 . The 1550 nm signal beam also gets refracted by the entrance interface of the spherical RR, then focused and reflected at the rear interface of the spherical RR, and ultimately re-collimated by the entrance interface of the spherical RR for its return back to its source.…”
Section: Device and System Designmentioning
confidence: 99%
“…The development of ultrafast pulsed lasers (pulse duration <1 ps) was a significant scientific achievement, with a plethora of applications including semiconductor characterization [1,2], optical interferometric studies [3,4], and material analyses [5], and was a key advancement to allow electromagnetic measurements over the terahertz (THz) spectrum [6][7][8][9]. The THz spectrum contains electromagnetic radiation in a frequency interval from 0.1 to 10 THz (corresponding to wavelengths from 3 mm to 30 µm, respectively) and is of great interest for science and technology.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrafast science and measurement of terahertz (THz) electromagnetic radiation is a rapidly-growing research area with many applications [1][2][3][4][5][6][7]. Terahertz electromagnetic radiation occupies a unique section of the electromagnetic spectrum, being 0.1-10 THz.…”
Section: Introductionmentioning
confidence: 99%